Differential Modulation of Heat-Inducible Genes Across Diverse Genotypes and Molecular Cloning of a sHSP From Pearl Millet [Pennisetum glaucum (L.) R. Br.] - Mukesh Sankar, S.; Tara Satyavathi, C.; Barthakur, Sharmistha; Singh, Sumer Pal; Bharadwaj, C.; Soumya, S. L. (Frontiers in Plant Science, 2021)
The survival, biomass, and grain yield of most of the crops are negatively influenced by several environmental stresses. The present study was carried out using transcript expression profiling for functionally clarifying the role of genes belongs to the small heat shock protein (sHSP) family in pearl millet under high-temperature stress. Transcript expression profiling of two high temperature-responsive marker genes such as Pgcp70 and PgHSF along with physio-biochemical traits in combination was considered to screen out the best contrasting genotypes among eight different pearl millet inbred lines at the seedling stage. Transcript expression pattern suggested the existence of differential response among different genotypes upon heat stress in the form of accumulation of heat shock responsive gene transcripts. Genotypes such as WGI 126, TT-1, TT-6, and MS 841B responded positively towards high-temperature stress for transcript accumulation of both Pgcp70 and PgHSF and also indicated a better growth under heat stress. PPMI-69 showed the least responsiveness to transcript induction; moreover, it supports the membrane stability index data for scoring thermo-tolerance, thereby suggesting the efficacy of transcript expression profiling as a molecular-based screening technique for the identification of thermo-tolerant genes and genotypes at particular crop growth stages. The contrasting genotypes such as PPMI-69 (thermo-susceptible) and WGI-126 and TT-1 (thermo-tolerant) are further utilized for the characterization of thermo-tolerance behaviour of sHSP by cloning a PgHSP16.97 from the thermo-tolerant cv. WGI-126. Further, the investigation was extended for the identification and characterization of 28 different HSP20 genes through a genome-wide search in the pearl millet genome and understanding their expression pattern using the RNA-seq dataset. The outcome of the present study indicated that transcript profiling can be a very useful technique for high throughput screening of heat-tolerant genotypes at the seedling stage. Also, identified PgHSP20s genes can provide further insight into the molecular regulation of pearl millet stress tolerance and bridging them together to fight against the unpredicted nature of abiotic stress.